Exploratory growth analysis of a megacity through different spatial metrics: a case study on Dhaka, Bangladesh (1960-2005) - Ahmed, Sohel; Bramley, Glen; Dewan, Ashraf (Urban and Regional Information Systems Association, 2012)
Recent advances and greater availability of geographic information systems (GIS) and remote-sensing (RS) technologies and data have opened wider possibilities for tackling many challenging issues of urban planning and management in developing countries, particularly in detecting, monitoring, analyzing, and modeling land-use and land-cover change (LUCC) patterns. Until recently, there has not been much evidence of use of GIS-RS tools in examining or monitoring rapidly expanding megacities such as Dhaka, the primary city of Bangladesh that had transformed 4,700 ha of agricultural and low-lying areas to urban areas during the period 1999-2005. The objective of this study was to explore and analyze the pattern of urban growth in the Dhaka megacity using remote sensing and spatial metrics. Multitemporal land-use/land-cover data have been acquired and used to determine urban growth in Dhaka. Using a number of spatial metrics, the study quantified spatial and temporal patterns of urban growth in Dhaka from 1960 to 2005.The study revealed that the total urban footprint increased rapidly to 20,551.0 ha (49.4 percent of the total land mass) in 2005 from 4,631.8 ha (11.1 percent) in 1961. The core hot spot of changes shifted from the central toward the north, south, east, and southeast directions in the 1990s and 2000s as exemplified initially by the trend surface, and later by the spatial metrics- detecting urban growth and its form in further details. Infill development was found to occur substantially even after sufficient consolidation already had taken place, which can be attributed primarily to the principal job and commercial hubs being located in the city core and, thus, shorter work-home trip lengths in Dhaka (also evident from the proximity and cohesion index). Analyses of patterns of urbanization can be linked to possible factors driving massive urban growth and, therefore, may be useful for making informed decisions for future sustainable urban planning and management of Dhaka megacity.